(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Rapid urbanisation and industrialization have resulted in two major consequences. The waste of resources and the accumulation of rubbish are two such examples. As people’s living standards rise, they produce vast quantities of municipal solid waste. This waste is then either sent to landfills or burned openly, polluting the air across the city. For this reason, it is essential to develop and execute a reliable solid waste management system that would help lessen the environmental damage caused by municipal landfills. With this in mind, the current investigation was conducted to learn more about the issues surrounding MSW dump sites close to the Banvhare Dada Nuwakot disposal facility in Nepal. The purpose of this research is to monitor and analyse land-based municipal solid waste problems and to evaluate the practicability of municipal solid waste energy recovery. At the dump site, the atmosphere and air quality were monitored, as well as soil and water tests. The quantity of leachate elements in the subsoil is also being determined as part of this investigation to help in future site appraisal. Results from a physical and chemical analysis of municipal solid waste (MSW) collected from the landfill showed that the landfill’s trash had a biodegradable fraction of 79 percent, a higher proportion of moisture levels, and a volatile solid content of 76 percent. Thus, bio-methanation of municipal solid waste may proceed. Cost effectiveness, resource conservation, reduced greenhouse gas emissions, and other benefits are all features of plastic soil brick. The "Eco Bricks" or plastic soil bricks, also known as, are formed of plastic waste and may be utilised for construction but are otherwise hazardous to all living things. Compared to bricks made of fly ash, it improves compressive strength. Alkalis’ water-absorbing capacity was significantly decreased by the usage of plastic soil blocks. Further study would enhance the quality and durability of plastic soil bricks because of their multiple benefits.